Behavioural, Pharmacokinetic, Metabolic, and Hyperthermic Profile of 3,4-Methylenedioxypyrovalerone (MDPV) in the Wistar Rat - Horsley, Rachel R.; Lhotkova, Eva; Hajkova, Katerina; Feriancikova, Barbara; Himl, Michal; Kuchar, Martin; Páleníček, Tomas (Frontiers in Psychiatry, 2018)
3,4-methylenedioxypyrovalerone (MDPV) is a potent pyrovalerone cathinone that is substituted for amphetamines by recreational users. We report a comprehensive and detailed description of the effects of subcutaneous MDPV (1 – 4 mg/kg) on pharmacokinetics, biodistribution and metabolism, acute effects on thermoregulation under isolated and aggregated conditions, locomotion (open field) and sensory gating (prepulse inhibition, PPI). All studies used male Wistar rats. Pharmacokinetics after single dose of 2 mg/kg MDPV was measured over six hours in serum, brain and lungs. The biotransformation study recorded 24 hour urinary levels of MDPV and its metabolites after 4 mg/kg. The effect of 2 mg/kg and 4 mg/kg on body temperature (°C) was measured over 12 hours in group- versus individually-housed rats. In the open field, locomotion (cm) and its spatial distribution were assessed. In PPI, acoustic startle response (ASR), habituation, and PPI were measured (AVG amplitudes). In behavioural experiments, 1, 2, or 4 mg/kg MDPV was administered 15 or 60 minutes prior to testing. Thermoregulation and behavioural data were analysed using factorial analysis of variance (ANOVA). Peak concentrations of MDPV in sera, lung and brain tissue were reached in under 30 minutes. While negligible levels of metabolites were detected in tissues, the major metabolites in urine were demethylenyl-MDPV and demethylenyl-methyl-MDPV at levels three-four times higher than the parent drug. We also established a MDPV brain/serum ratio ~2 lasting for ~120 minutes, consistent with our behavioural observations of locomotor activation and disrupted spatial distribution of behaviour as well as moderate increases in body temperature (exacerbated in group-housed animals). Finally, 4 mg/kg induced stereotypy in the open field and transiently disrupted PPI. Our findings, along with previous research suggest that MDPV is rapidly absorbed, readily crosses the blood-brain barrier and is excreted primarily as metabolites. MDPV acts as a typical stimulant with modest hyperthermic and psychomimetic properties, consistent with a primarily dopaminergic mechanism of action. Since no specific signs of acute toxicity were observed, even at the highest doses used, clinical care and harm-reduction guidance should be in line with that available for other stimulants and cathinones.